Penatalaksanaan Fisioterapi Pada Kasus Down Syndrome di Pediatric Neurodevelopmental Treatment Centre (PNTC) Karanganyar - Maksum, Muhammad Ridho; , Umi Budi Rahayu, S.Fis. M.Kes (2016)
Background: Down Syndrome is a condition of physical and mental retardation caeused by developmental abnormalities of chromosome. These chromosomes are formed as a result of the failure of a pair of chromosomes to separate from one another when division occurs. Clinical manifestations of Down Syndrome is mental retardation, typical physical characteristics, and developmental delay. One method that can be used to treat developmental disorders children with Down Syndrome is Neuro Developmental Treatment(NDT). Aim: To find out isNeuro Developmenetal Treatment (NDT) can improve tone and strength of muscle in the upper and lower limbs, the ability to functional activity, and gross motor skills in patients with Down Syndrome condition. Result: after 6 treatment, there is some improvement in muscle tone in the second region of the cervical, thoraco-lumbar, shoulder, elbow, and wrist from T4: positive hipotonus to T5: negative hipotonus.XOTR scale showed increased muscle strength both region of shoulder, elbow, and wrist from T4: Trace (T) to T5: powerful contraction (X). DDST showed an increase of the normal score from T1: 31 to T6: 39. GMFM showed an increase in the percentage from T1: 23.82% to T6: 32.54%. Conclusion: Neuro Developmental Treatment (NDT) can improve muscle tone, increase muscle strength, improve ability to functional activity and gross motor skills of patients with Down Syndrome.